Strategic Financial Decision-Making Among Young Indonesian Investors: A Behavioral Perspective on Cryptocurrency Rein-vestment - Reddy Chandra; Ferdi Antonio; Laurens Kaluge (Qubahan Academic Journal)
This study investigates behavioral factors that shape the intention to reinvest in cryptocurrency among young investors in Jakarta, Indonesia. The research adopts a conceptual framework based on the Theory of Planned Behavior (TPB) and the Theory of Interpersonal Behavior (TIB), combining rational variables such as financial literacy and financial influencer with emotional variables including swift benefit and cognitive biases. A total of 528 valid responses were collected through an online survey and analyzed using PLS-SEM. The results indicate that positive sentiment (β = 0.477) and control belief (β = 0.331) have a significant impact on reinvestment intention. Emotional factors show stronger indirect effects through these mediators compared to rational factors. In addition, perceived technological advancement plays a moderating role by significantly enhancing the effect of control belief on reinvestment intention (β = 0.208), while reducing the influence of positive sentiment (β = -0.458). These findings suggest that emotional responses are more dominant than rational evaluations in guiding reinvestment decisions in volatile digital markets. The integration of TPB and TIB provides a theoretical contribution to the field of behavioral finance and offers practical recommendations for improving investor literacy, platform engagement strategies, and regulatory support in the cryptocurrency ecosystem.